PENGEMBANGAN BAHAN AJAR UNTUK MENUMBUHKAN KREATIFITAS BERWIRAUSAHA MAHASISWA DI FKIP: PENGEMBANGAN BAHAN AJAR UNTUK MENUMBUHKAN KREATIFITAS BERWIRAUSAHA MAHASISWA DI FKIP - Andini, Andini (Journal of Business Education and Social, 2022)
The development of teaching materials is one of the driving aspects in the learning process so that learning can be active. Entrepreneurship learning is one way to grow students to be more creative in creating works of art. This study aims to find out how to develop teaching materials to foster entrepreneurial creativity for FKIP students. This research method uses a qualitative method with a descriptive approach by conducting interviews to gather information for 4 days. The subjects of this study were Lecturers and Students of FKIP Unis. The results of the study explain that the development of teaching materials in the form of lesson plans or syllabus as well as expert guidelines and guidebooks to motivate students to be creative with the work they create. Keywords: Developing of Teaching Materials, Creativity, Entrepreunership.